CD8+ T cells provide immune protection against murine disseminated endotheliotropic Orientia tsutsugamushi infection. - Guang Xu; Nicole L Mendell; Yuejin Liang; Thomas R Shelite; Yenny Goez-Rivillas; Lynn Soong; Donald H Bouyer; David H Walker (PLoS Neglected Tropical Diseases, 2017)
Scrub typhus, caused by a Gram-negative obligately intracellular coccobacillus, Orientia tsutsugamushi, is a long neglected but important tropical disease. Orientia tsutsugamushi causes illness in one million people each year, and 1 billion people are at risk. Without appropriate diagnosis and treatment, the disease can cause severe multiorgan failure with a case fatality rate of 7-15%. The current gaps in knowledge of immunity include the unknown mechanisms of host immunity to O. tsutsugamushi. Using an intravenous (i.v.) disseminated infection mouse model, we observed that more CD8+ T cells than CD4+ T cells were present in the spleen of infected mice at 12 dpi. We also determined that Treg cells and the proportion of T cells producing IL-10 were significantly increased from 6 dpi, which correlated with the onset of illness, body weight loss, and increased bacterial loads. We further studied CD8-/-, MHC I-/- and wild type control (WT) C57BL/6J mice to determine the importance of CD8+ T cells and MHC I molecules. After infection with an ordinarily sub-lethal dose of O. tsutsugamushi, all CD8-/- and MHC I-/- mice were moribund between 12 and 15 dpi, whereas all WT mice survived. Bacterial loads in the lung, kidney, liver and spleen of CD8-/- and MHC I-/- mice were significantly greater than those in WT mice. Interferon-γ (IFN-γ) and granzyme B mRNA levels in the liver of CD8-/- and MHC I-/- mice were significantly greater than in WT mice. In addition, more severe histopathologic lesions were observed in CD8-/- mice. Finally, adoptive transfer confirmed a major role of immune CD8+ T cells as well as a less effective contribution by immune CD8 T cell-depleted splenocytes in protection against O. tsutsugamushi infection. These studies demonstrated the critical importance of CD8+ T cells in the host immune response during O. tsutsugamushi infection.